2009
DOI: 10.1111/j.1365-2958.2009.06907.x
|View full text |Cite
|
Sign up to set email alerts
|

The γ‐glutamylcysteine synthetase gene of Leishmania is essential and involved in response to oxidants

Abstract: SummaryGamma-glutamylcysteine synthetase, encoded by the GSH1 gene, is the rate-limiting enzyme in the biosynthesis of glutathione and of trypanothione in Leishmania. The importance of GSH1 was assessed by generating GSH1 null mutants in Leishmania infantum. Removal of even a single wild-type allelic copy of GSH1 invariably led to the generation of an extra copy of GSH1, maintaining two intact wild-type alleles. However, by first supplementing the parasites with a rescue plasmid, we succeeded in obtaining both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 61 publications
3
59
0
Order By: Relevance
“…The importance of oxidative stress responses in the virulence and survival of pathogens in their natural environment has been suggested by many studies, but the relative importance of the glutathione-dependent redox pathway, as opposed to other pathways for redox homeostasis and oxidative stress, has not been rigorously evaluated. In parasitic protozoans such as Leishmania infantum and Trypansoma brucei, however, glutathione biosynthesis (which leads to trypanothione synthesis), is essential (Huynh et al, 2003;Mukherjee et al, 2009), while in the malarial parasite Plasmodium berghei, glutathione biosynthesis has been shown to be essential for the survival of the protozoan during its passage through insects (VegaRodríguez et al, 2009). Further, in L. infantum, even the deletion of one of the two copies of the GSH1 gene is not tolerated by the organism.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of oxidative stress responses in the virulence and survival of pathogens in their natural environment has been suggested by many studies, but the relative importance of the glutathione-dependent redox pathway, as opposed to other pathways for redox homeostasis and oxidative stress, has not been rigorously evaluated. In parasitic protozoans such as Leishmania infantum and Trypansoma brucei, however, glutathione biosynthesis (which leads to trypanothione synthesis), is essential (Huynh et al, 2003;Mukherjee et al, 2009), while in the malarial parasite Plasmodium berghei, glutathione biosynthesis has been shown to be essential for the survival of the protozoan during its passage through insects (VegaRodríguez et al, 2009). Further, in L. infantum, even the deletion of one of the two copies of the GSH1 gene is not tolerated by the organism.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage infection was performed as described previously, with minor modifications (Pal et al, 2015;Mukherjee et al, 2009). Briefly, J774A.1 macrophages were activated with 100 ng/ml lipopolysaccharide to enhance their chemotactic and phagocytic abilities (Wu et al, 2009).…”
Section: Macrophage Infection and Determination Of Intracellular Paramentioning
confidence: 99%
“…Targeted gene disruption is achievable in Leishmania by homologous recombination of linear DNA and it is a powerful and effective tool for genetic functional studies in the parasite [82]. Since gene replacement and double gene knockout strategies have been established in Leishmania [74,83], several essential and non-essential genes have been knocked-out and phenotypic changes have been analyzed [84][85][86][87][88]. Some of these studies confirmed the complexity of issues such as virulence, infectivity or pathogenesis [33][34][35][36].…”
Section: Forward and Reverse Geneticsmentioning
confidence: 95%